2012
DOI: 10.1002/ijc.27772
|View full text |Cite
|
Sign up to set email alerts
|

A novel role for junctional adhesion molecule‐A in tumor proliferation: Modulation by an anti‐JAM‐A monoclonal antibody

Abstract: To identify new potential targets in oncology, functional approaches were developed using tumor cells as immunogens to select monoclonal antibodies targeting membrane receptors involved in cell proliferation. For that purpose cancer cells were injected into mice and resulting hybridomas were screened for their ability to inhibit cell proliferation in vitro. Based on this functional approach coupled to proteomic analysis, a monoclonal antibody specifically recognizing the human junctional adhesion molecule-A (J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
47
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 43 publications
4
47
0
Order By: Relevance
“…Previous research showed that low levels of JAM-A in the normal lung tissues are detected, compared with cancer tissues, but prognostic analysis is not performed. 5 Therefore, our research fills the gaps in this field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research showed that low levels of JAM-A in the normal lung tissues are detected, compared with cancer tissues, but prognostic analysis is not performed. 5 Therefore, our research fills the gaps in this field.…”
Section: Discussionmentioning
confidence: 99%
“…3 Junctional adhesion molecules (JAMs), members of immunoglobulin superfamily proteins, are located at the lateral membrane of endothelial and epithelial cells. 4 Recent studies showed that dysregulation of junctional adhesion molecule-A (JAM-A), an important component of JAMs as well as TJs, is associated with cancer progression, 5 demonstrating that potential clinical values in cancers. However, the exact roles and clinical significances of JAM-A in cancers remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Another exciting potential target is JAM-A, given the positive association between its overexpression and poor prognosis in breast cancer patients 91 , 92 , 94 and following a recent publication demonstrating anti-proliferative efficacy of a function-blocking JAM-A antibody in xenograft murine models of breast cancer 221 . Unpublished work from our group has also shown promising in vitro and pre-clinical in vivo efficacy of a novel small molecule inhibitor of JAM-A, which we sp.eculate could be particularly valuable in aggressive breast cancers concomitantly overexpressing HER2 and JAM-A.…”
Section: Clinical Application Of Adhesion Molecules In Breast Cancermentioning
confidence: 99%
“…Further evidence implicating JAM-A in breast cancer cell survival signaling has accrued from a study in which it was described as a novel regulator of HER2 protein degradation and signaling (15). In terms of the therapeutic potential of targeting JAM-A, its pharmacological inhibition using a monoclonal antibody has been demonstrated to significantly inhibit tumor growth in murine xenograft models of human tumors (17).…”
Section: Junctional Adhesion Molecules (Jams)mentioning
confidence: 99%